The Relationship Between Gasoline Exposure and Respiratory Complaints in Coastal Communities in Kurnia Village - Lauchan, Agil maritho; Nanda, Meutia; Amrainum, Desri; Saragih, Eka Fitria; Sinambela, Nur Delina (Universitas Ibn Khaldun Bogor, 2024)
Gasoline is one of the factors that can affect human health that is often found in the community, one of which is from exposure to gasoline itself. Gasoline can have an impact on reducing air quality and can have an effect on health problems, especially in breathing. This study aims to determine gasoline exposure with complaints of respiratory problems in the community of Kampung Kurnia, Belawan Bahari Village. This study used quantitative methods with a cross sectional research design. The results showed that the Pvalue obtained was 0.046 which or <0.05 which means that there is exposure to gasoline with complaints of respiratory problems in coastal communities in Kampung Kurnia, Belawan Bahari Village.